1987
DOI: 10.1093/nar/15.4.1543
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of cauliflower mosaic virus 35S and nopaline synthase promoters in transgenic plants

Abstract: We have compared the level of expression of the Cauliflower Mosaic Virus 35S promoter and the nopaline synthase promoter when fused to a common reporter gene. A cassette containing the neomycin phosphotransferase (type II) coding sequence followed by the nopaline synthase 3' nontranslated region was used for transcriptional and translational evaluation of the two different promoters. These chimeric genes were introduced into petunia plants and the copy number of the gene, the steady state level of NPTII transc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

13
108
0

Year Published

1987
1987
2014
2014

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 213 publications
(121 citation statements)
references
References 51 publications
13
108
0
Order By: Relevance
“…In plants containing the fusion genes, GUS activity was localized primarily in cotyledons, with some activity present in the hypocotyl. As controls, we showed that nontransformed seedlings did not stain for GUS activity and, as shown in Figure 3D, that a GUS fusion gene driven by the 355 promoter of cauliflower mosaic virus was expressed differently from the isocitrate lyase and malate synthase fusion genes (Sanders et al, 1987). We also measured GUS activities at different stages of postgerminative growth in plants containing each of the fusion genes and showed that these time courses correlated with modulations in isocitrate lyase and 'malate synthase enzyme activities in B. napus and tobacco (data not shown; Ettinger and Harada, 1990).…”
Section: Regulated Activities Of Lsocitrate Lyase and Malate Synthasementioning
confidence: 82%
“…In plants containing the fusion genes, GUS activity was localized primarily in cotyledons, with some activity present in the hypocotyl. As controls, we showed that nontransformed seedlings did not stain for GUS activity and, as shown in Figure 3D, that a GUS fusion gene driven by the 355 promoter of cauliflower mosaic virus was expressed differently from the isocitrate lyase and malate synthase fusion genes (Sanders et al, 1987). We also measured GUS activities at different stages of postgerminative growth in plants containing each of the fusion genes and showed that these time courses correlated with modulations in isocitrate lyase and 'malate synthase enzyme activities in B. napus and tobacco (data not shown; Ettinger and Harada, 1990).…”
Section: Regulated Activities Of Lsocitrate Lyase and Malate Synthasementioning
confidence: 82%
“…pPRO1-derived plasmids were digested with BglII and EcoRI, and the inserts containing the ORF were purified and ligated into the polylinker region of the plasmid pMON316, digested with the same two restriction enzymes. In this position, the coding sequence is placed between the CaMV 35S promoter and the nopaline synthase 3h untranslated region (Sanders et al, 1987). Leaf disks of N. tabacum cv.…”
Section: Methodsmentioning
confidence: 99%
“…1B), the sequence was excised from a pUC-type plasmid (13), end-filled with deoxynucleotides by using the Klenow fragment of DNA polymerase I, and then ligated to the intermediate plasmid pMON316 (14) (16). Three independent transformants containing anti-A sequences and one containing anti-B sequences were used for analysis.…”
mentioning
confidence: 99%